Study on incidence and clinical profile of anemia in children aged 1 years to 15 years attending tertiary care hospital - Nekkanti, Chaitra; M., Pranam G.; H., Usha; Chetty , Sanjeev (International Journal of Contemporary Pediatrics, 2024)
Background: Children are considered as an important asset for any country and their health as one of the important indicators of a healthy country. There are various factors influencing children’s health, with anemia being one of them. Anemia is a major global health problem, especially in developing countries like India, despite the fact that this problem is largely preventable and easily treatable. Methods: It is a descriptive study conducted in 140 children aged 1 year to 15 years who presented with anemia in the department of pediatrics at Navodaya Medical College Hospital and Research Center, Raichur. Aim was to study the incidence and profile of anemia in children aged 1 years to 15 years. Results: A total 0f 140 cases aged between 1- 15 years were included in the study. The highest number of cases occurred in the 11-15 years age group (38.5%), followed by the 6-10 years group (35.0%). There is more female preponderance in this study (55.7%) compared to males (44.2%). Moderate degree of anemia was the commonest grade of anemia (42.8%) The most common cause of anemia in this study was iron deficiency, accounting for 58 cases (41.4%) followed by 17 cases (12.1%) had megaloblastic anemia. Conclusions: Iron deficiency anemia is a preventable cause of cognitive impairment, and early interventions can prevent the morbidity and mortality associated with anemia. Despite the implementation of national programs to combat iron deficiency, the problem persists. Early detection of anemia among these children enables the planning of suitable interventions, such as nutritional education for mothers, growth monitoring, nutritional supplementation, deworming, and more, to effectively address and mitigate the issue.